Tractable Cre-lox system for stochastic alteration of genes in mice - Miller, Ashleigh J (2008)
We developed a cell division–activated Cre-lox system for stochastic recombination of loxP-flanked loci in mice. Cre activation by frameshift reversion is modulated by DNA mismatch-repair status and occurs in individual cells surrounded by normal tissue, mimicking spontaneous cancer-causing mutations. This system should be particularly useful for delineating pathways of neoplasia, and determining the developmental and aging consequences of specific gene alterations.